Dynamics of Phosphorus Fractions and Chemical Properties of Paddy Soils as related to Paddy Rice Cropping Index and Irrigation Practices: Dinamika Fraksi Fosfor dan Sifat Kimia Tanah Sawah Terkait Indeks Pertanaman Padi Sawah dan Praktik Pengairan - Sudadi, Untung; Ramadhan, Laode Muhamad Asdiq Hamsin; Nugroho, Budi; Hartono, Arief (Jurnal Ilmu Tanah dan Lingkungan, 2019)
Dynamics of P fractions and other chemical properties of paddy soil are related to paddy rice cropping index (CI) and soil water content at field conditions (SFWC).  This explorative research was aimed at evaluating the effects of different CIs represented by ameliorations and fertilizations applied by, and SFWC to represent irrigation practiced by farmers of the studied paddy soils on dynamics of P fractions, other soil chemical properties, and paddy rice yield. Composite soil samples were taken from cultivated paddy fields with CI 100%, 200%, and 300% at 7, 9, 11, and 13 weeks after the initial waterlogging. Soil P was fractionated into soil PH2O, PNaHCO3-inorganic (Pi), PNaHCO3-organic (Po), PNaOH-Pi, PNaOH-Po, and PHCl fractions. At the four soil sampling times, SFWC at CI 100% < 200% ≈ 300%. At CI 100%, soil Po fractions tended to decrease, whilst Pi fractions tended to increase with the increasing SFWC. Soil P dynamics in all CIs were predominantly determined by Corg. Increase in Corg decreased Pi fractions at CI 100% and Po fractions at CI 200% but increased Pi fractions at CI 300%. Decreasing P2O5 and increasing rice straw doses decreased soil Eh. The predominant factor affected rice paddy yield was SFWC.  Keywords: P fertilizer, rice straw, soil field water-content, soil P fractions